Race/Ethnicity and Age Distribution of Breast Cancer Diagnosis in the United States - Stapleton, Sahael M. (JAMA Surg, 2018)
This study assesses the age distribution of breast cancer diagnosis across race/ethnicity in US female patients using the Surveillance, Epidemiology, and End Results Program database.